DEVELOPING CALCULATING ABILITY FOR CHILDREN WITH COGGLAK TRADITIONAL GAMES: MENGEMBANGKAN KEMAMPUAN BERHITUNG PADA ANAK DENGAN PERMAINAN TRADISIONAL CONGKLAK - ANDRIKA MUJI LESTARIA; MADE AYU ANGGRENI (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2020)
This research is motivated by the information that the traditional game congklak is considered to improve the children’s ability to count . The traditional game congklak is one of the learning media that can improve the children’s capability to count. With traditional congklak games it is expected that children can learn to count in a more enjoyable way. The problem formulation in this research is